Implementação do gerenciamento de riscos operacionais na área de recebimento integrado: uma abordagem intervencionista em uma editora nacional - Moraes, Wilson de (2017)
Risk management is one of the most important features for the survival of organizations. In a background in which transparency and reliability are fundamental cornerstones in financial statements, appropriate management of operational risks is a growing concern. As a result, risk management is increasingly necessary and a vital tool to reduce the opportunities for deviations from the route plan. However, the literature on the subject addresses, mainly, companies in the financial sector, showing a lack of data for organizations in other industries. Within this context, this study aims to present the implementation of operational risk management in the Integrated Receiving (IR) area of a National Publisher. The analysis of this study was based on the concepts of COSO (Committee of Sponsoring Organizations of the Treadway Commission) methodology and made possible using Control Self Assessment (CSA) methodology, in addition to the interventionist approach. CSA methodology provides the identification of risks by managers of the area under analysis. However, in order to develop a theoretical contribution, this study analyzed data referring to employees in IR area. After data were collected, the implementations of the necessary corrective actions were discussed and negotiated with the concerned manager. The result was a success throughout the whole process of implementation; in addition, the participation of all employees were beneficial and constructive for the company in order to determine weaknesses of the area. The main benefit observed was the dissemination of the risk culture among the participants of this work and an improvement in the control environment for the company. Results should be analyzed considering the limitations of this work, as the company studied belongs to a specific sector. Therefore, as a suggestion for future research, there is a need to expand the number of companies and internal areas to be studied, comparing the conclusions with those of this study.